Metody analizy łącznej i wyborów dyskretnych - podobieństwa i różnice - Bąk, Andrzej (Conjoint Analysis and Discrete Choice Methods - Similarities and Differences, 2006)
Decompositional approach is one of the often used in stated consumer preferences research. In this case the analytical methods are based on data collected a priori by means of surveys to register intentions stated by consumers at the moment of survey taking. The methods used in decompositional approach include conjoint analysis and discrete choice methods. In this paper outlines of both groups methods are given. Next, some similarities and differences between both groups are briefly described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 31-42